Random Laser Emission from Fiber coated ZnO - Ali A.T.; Kamil W.M.W.A.; Wu S.-C.; Yang C.-X.; Hsu H.-C.; Adikan F.R.M.; Mahdiraji G.A.; Abdullah F. (Penerbit Universiti Sains Malaysia, 2024)
Random lasing from a solid-state gain medium prepared on photonic crystal fibre (PCF) is observed for the first time. Vertically aligned ZnO microrods were prepared on PCF using a simple technique of chemical bath deposition (CBD). A low lasing threshold of 12.2 mJ/cm2 was observed in sample with longer zinc oxide (ZnO) rod length. The variation in morphology and population density did not affect the lasing threshold significantly. Further investigation of the effect of fiber length revealed that a shorter fiber had a lower threshold and showed quenching of the spontaneous emission revealing better lasing output. Simulations based on the morphology of the gain medium revealed light confinement in the structure, validating the origin of the lasing emission. Overall, this study shows the potential of utilising optical fiber as random lasers with a sustainable solid state gain medium. Penerbit Universiti Sains Malaysia, 2023. This work is licensed under the terms of the Creative Commons Attribution (CC BY) (http://creativecommons.org/licenses/by/4.0/).